(untitled) (Editora Impacto Científico, 2025)
Primary Health Care (PHC) is the main gateway and coordinating center of the health care network. In the context of the Unified Health System, the Family Health Strategy (ESF) was implemented with the aim of operationalizing PHC, promoting the reorganization of care levels and contributing to improving access to and the quality of the services offered. Quality PHC has a positive impact on the population’s health indicators, being able to prevent diseases, minimize the severity of illnesses and reduce complications. In this scenario, this study, through a literature review, aimed to identify the main factors that lead users with PHC-sensitive conditions to seek care in urgent and emergency services. The results showed weaknesses related to the lack of information and resources available to users, health teams and municipal management, which compromises the effectiveness of rational care flows within the health care network.